RITUAL “NGABEN” DI KAMPUNG BALI DESA BELUTU, KECAMATAN KANDIS, KABUPATEN SIAK, PROVINSI RIAU - Indah Hotmaria Hutapea; I Nyoman Suarsana; I Ketut Kaler (CV. Alim's Publishing, 2024)
The island of Bali is a paradise for culture, every activity in Bali will never escape its cultural touch. Not only marriage, birth, but until death. Almost all Indonesian people and even foreign countries must have known and are familiar with every ritual that is owned by the people who live on the island of Bali. An example is the cremation ritual. Ngaben is one of the Balinese Hindu traditions to carry out death ceremonies. According to Tattwa, a person is considered dead if his atma has been separated from the five maha bhuta, this is mentioned in vrasphati tattwa (Swastika: 2008). The Ngaben ritual is carried out with a long series of activities and invites many people. In addition, this ritual also requires a relatively large range of costs. Because this death ritual is different from death rituals with other tribes, where most of the death rituals in various tribes in Indonesia are only carried out by directly burying the body. However, cremation is done by burning the corpse.